A sulfur-containing lithium battery positive electrode material and preparation method thereof and lithium battery

Through the liquid phase doping method of anionic sulfur, the problem of unstable existing lithium-rich manganese-based positive electrode materials under high magnification and high temperature conditions is solved, and the cycle stability and rate performance is achieved, which promotes lithium-ion batteries performance improvement.

CN115275193BActive Publication Date: 2025-02-14PEKING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110483025.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2025-02-14
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based cathode materials exhibit unstable cycling performance and capacity decay under high magnification and high temperature conditions, and fail to effectively achieve anionic sulfur doping, limiting their commercial applications.

Method used

Sulfur is doped as anion into the lithium-rich manganese-based positive electrode material by liquid phase method to form a chemical structure of Li1+δMnaNibCocSxOy, using the covalent action of anions and metals to inhibit oxygen redox activity and improve the cyclic stability and rate performance of the material. .

Benefits of technology

It significantly improves the cycle stability and high temperature stability of the positive electrode material, while improving the rate performance and discharge capacity, achieving higher energy density and better battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275193B_ABST
    Figure CN115275193B_ABST
Patent Text Reader

Abstract

The present invention discloses a sulfur-containing lithium battery positive electrode material and a preparation method thereof and a lithium battery. The sulfur-containing lithium battery positive electrode material is a lithium-rich manganese-based positive electrode material doped with anionic sulfur, and the chemical formula is Li 1+δ Mn a Ni b Co c S x O y , wherein δ=0~0.2, a=0.45~0.7, b=0.05~0.35, c=0.05~0.3, x=0.001~0.1, y=1.9~1.999, and x+y=2, δ+a+b+c=1; the undoped sulfur positive electrode material is fully reacted and dried in a solution containing anionic sulfur by a liquid phase method. In the positive electrode material of the present invention, since the anionic sulfur has a chemical bond with a tighter binding ability with the metal and a larger lattice, a more stable anion redox and a faster lithium ion migration ability are achieved, and finally the modified lithium-rich manganese-based positive electrode material has a high cycle stability and rate performance. In addition, the liquid phase method of doping sulfur elements used in the present invention has simple synthesis steps, is easy to operate, and does not require sintering at high temperature, and has the ability of large-scale production and the advantages of energy saving and emission reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a sulfur-containing lithium battery positive electrode material and a preparation method thereof, and a lithium battery. Background Art

[0002] The global energy crisis and increasingly serious environmental pollution have made it necessary to develop grid storage, transportation and portable devices based on clean energy. As a clean energy, the new lithium-ion battery has the advantages of high safety, good cycle performance, long life, environmental friendliness and recyclability.

[0003] Lithium-ion batteries generally include an anode, a cathode, a separator and an electrolyte. Lithium-ion batteries generally have a carbon negative electrode (or anode) and a transition metal oxide positive electrode (or cathode). The cathode and anode are generally layered structures to accommodate lithium ions, which are transferred between the cathode and anode for energy transfer during charging and discharging.

[0004] As an important component of lithium-ion batteries, positive electrode materials are key factors in determining battery safety, capacity and price. In terms of price, in the current commercially produced lithium-ion batteries, the cost of positive electrode materials accounts for about 20%-40% of the total battery cost. The reduction in the price of positive electrode materials directly determines the reduction in the price of lithium-ion batteries, especially for power lithium-ion batteries used in new energy vehicles. In addition, lithium-ion batteries, especially power lithium-ion batteries, have special requirements in terms of large current discharge, specific energy, safety, etc., and the positive electrode materials currently being studied or applied have not fully met the requirements, which has greatly restricted the development of lithium-ion power batteries.

[0005] The positive electrode of the first generation of lithium-ion batteries is lithium cobalt oxide (LiCoO2), which is a layered compound in which oxygen atoms are densely packed. This structure forms octahedral voids equivalent to the number of oxygen atoms. Transition metal layers and lithium layers are arranged alternately in the structure. Lithium cobalt oxide has weak high-voltage stability. When half of the lithium is removed from the lithium cobalt oxide (voltage is higher than 4.3V), the layered compound becomes unstable due to oxygen loss. The high price of cobalt increases the cost of lithium cobalt oxide. By adding nickel and manganese elements, its performance and cost are further optimized. This optimized positive electrode material is called a ternary material (NCM).

[0006] The original ternary material is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (NCM333). To increase the capacity, the improvement of the structure and composition of ternary materials is carried out in two directions. One is to increase the nickel content, reduce the cobalt content, and enhance the stability of the layered structure. The other is to increase the relative contents of lithium and manganese, such as the lithium-rich manganese-based materials proposed by Argonne National Lab. In this kind of material, lithium occupies positions in the transition metal layer to form a lithium-rich phase, and the lithium-rich phase and the non-lithium-rich phase form an atomic-level solid solution or a nano two-phase structure. This material has the general formula xLiMO2-(1-x)Li2MnO3, where 0 < x < 1, and M is one or more ions.

[0007] The performance of lithium-rich manganese-based cathode materials is related to their composition, especially to the content of Li2MnO3. A high Li2MnO3 composition can bring higher capacity, which is due to the introduction of the Li-O-Li configuration in the material and the oxygen redox reaction. However, the oxygen redox reaction also brings irreversible oxygen release and side reactions with the electrolyte, resulting in a decrease in its Coulombic efficiency, a decline in stability, voltage decay, and poor rate performance, etc., which has led to the delay in its commercialization. Therefore, there is an urgent need to provide a stable and high-rate lithium-rich manganese-based material.

[0008] Appropriate anion sulfur doping to replace the lattice oxygen site can inhibit the irreversible degree of oxygen redox in the material, increase the lattice spacing, improve the conductivity, etc., so it can improve the specific capacity density and rate performance of the cathode material. However, due to the easy oxidation of anion sulfur, the doping of sulfur anions is difficult to achieve experimentally. The existing sulfur-containing cathode materials mainly dope polyanion groups of sulfur into the lattice bulk phase and the surface, where sulfur is in a positive valence state. Sulfate ions can inhibit the contact between the material and the electrolyte, reduce side reactions, and improve the conductivity of the material, so it has a certain improvement on stability and rate performance. For example, Kang et al. doped nickel sulfate into the lithium-rich material, and the cycling stability at 1C for 250 cycles was about 78% (ACS Appl. Mater. Interfaces 2020, 12, 12, 13996–14004). Zhang et al. constructed surface oxygen vacancies by forming manganese sulfate compounds on the surface, and the voltage decayed to 2.77V after 200 cycles, which was an improvement compared with the 2.48V decay of the original material (ACS Appl. Mater. Interfaces 2020, 12, 38, 42660–42668). However, these sulfur-containing cathodes are all based on the doping and coating of sulfur in the form of positive polyanions, and sulfur is not doped into the lattice in the form of negative anions, so the modification effect on the cathode material is relatively limited. On the other hand, the polyanion sulfate itself does not have redox activity and will cause a loss of capacity of the cathode material. Based on the above existing sulfur-containing cathode materials, there is no report on anion sulfur-doped lithium-rich cathode materials yet. Summary of the invention

[0009] The purpose of the present invention is to address the deficiencies of the prior art and provide a sulfur-containing lithium battery positive electrode material having high energy density and high discharge capacity during the battery charge and discharge process. In the technical solution of the present invention, sulfur is doped into the positive electrode material as an anion. Through the enhancement of the covalent action between the anion and the metal, on the one hand, the activity of oxygen redox is suppressed, the side reactions at the interface are reduced, and the cycle stability and high temperature stability of the positive electrode material are greatly improved; on the other hand, due to the large size effect of anionic sulfur, the rate performance of the positive electrode material is significantly improved.

[0010] The present invention also aims to provide a method for preparing the above-mentioned lithium battery positive electrode material.

[0011] Another object of the present invention is to provide a lithium battery comprising the above-mentioned lithium battery positive electrode material. The lithium battery based on the above-mentioned sulfur-containing positive electrode material has good cycle performance and high rate.

[0012] The purpose of the present invention is achieved through the following technical solutions.

[0013] A sulfur-containing lithium battery positive electrode material, which is a lithium-rich manganese-based sulfur-doped positive electrode material with a chemical formula of Li 1+δ Mn a Ni b Co c S x O y , wherein δ=0~0.2, a=0.45~0.7, b=0.05~0.35, c=0.05~0.3, x=0.001~0.1, y=1.9~1.999, and x+y=2, δ+a+b+c=1; wherein sulfur is in the form of anion (S n- ) form in the material. This sulfur-containing positive electrode material is prepared by fully reacting the undoped sulfur positive electrode material in a solution containing anionic sulfur by a liquid phase method and then drying it.

[0014] In the sulfur-containing lithium battery positive electrode material of the present invention, sulfur is in the form of anions S n- Yes, in many cases 0 <n≤2。

[0015] Preferably, the above-mentioned sulfur-containing lithium battery positive electrode material Li 1+δ Mn a Ni b Co c S x O y In, δ=0~0.2, a=0.45~0.7, b=0.05~0.35, c=0.05~0.3, x=0.001~0.05, y=1.95~1.999.

[0016] Preferably, a solid solution or a nano-hybrid that forms two phases is formed in the above sulfur-containing lithium battery cathode material, that is, zLiMO y S 2-y -(1-z)Li2MnO y S 2-y , where 0 < z < 1, M is a combination of metal elements with a valence higher than 2+ including Ni, Co, and Mn, and y = 1.9 to 1.999.

[0017] Preferably, the above sulfur-containing lithium battery cathode material is charged and discharged at 30 °C, 2.1 to 4.8 V, and 0.1 C, and the discharge capacity is greater than 300 mAh / g.

[0018] Preferably, the above lithium battery cathode material is charged and discharged at 30 °C, 2.1 to 4.8 V, and 1 C, and the discharge capacity is more than 80% of the discharge capacity at 0.1 C.

[0019] The present invention also provides a preparation method of the above sulfur-containing lithium battery cathode material. The lithium-rich manganese-based lithium battery cathode material is added to a solution containing anionic sulfur for liquid-phase reaction, stirred evenly, filtered, and the sulfur-containing lithium battery cathode material is obtained and dried in vacuum.

[0020] In the above preparation method, the solution containing anionic sulfur is obtained by dissolving a soluble salt of sulfur in a solvent. The soluble salt of sulfur is preferably a sulfide, including but not limited to anhydrous sodium sulfide, sodium sulfide nonahydrate, thiourea, thioacetamide, etc.; the solvent includes one or more of water and ethanol.

[0021] Preferably, the concentration of the solution containing anionic sulfur is 0.01 mol / L to 0.5 mol / L, and the anionic sulfur can be S 2- etc.

[0022] In the above preparation method, the general formula of the lithium-rich manganese-based lithium battery cathode material is Li 1+δ Mn a Ni b Co c O2, where δ = 0 to 0.2, a = 0.45 to 0.7, b = 0.05 to 0.35, c = 0.05 to 0.3, and δ + a + b + c = 1.

[0023] Preferably, the concentration range of the lithium-rich manganese-based lithium battery cathode material in the solution containing anionic sulfur is 0.002 to 0.01 g / mL.

[0024] Preferably, the stirring speed of the liquid-phase reaction is 300 to 500 rpm, the reaction temperature is 30 to 40 °C, and the time is 0.5 to 1 hour.

[0025] Preferably, the vacuum drying temperature is 100-150° C., and the drying time is 12-24 hours.

[0026] The present invention also provides a lithium ion battery, comprising a positive electrode material, a negative electrode material, a separator and an electrolyte, wherein the positive electrode material is the above-mentioned sulfur-containing lithium battery positive electrode material.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The present invention is the first to dope sulfur into lithium-rich manganese-based positive electrode materials by liquid phase method, achieving sulfur doping in the form of anions. Compared with existing sulfur-containing positive electrode materials, the present invention synthesizes lithium-rich manganese-based positive electrode materials with anionic sulfur. Anionic sulfur has a chemical bond with a tighter binding ability with metals, and has a larger lattice, thereby achieving more stable anion redox and faster lithium ion migration ability, and ultimately making the modified lithium-rich manganese-based positive electrode material have high cycle stability and rate performance. In addition, the liquid phase method of doping sulfur elements used in the present invention has a relatively simple synthesis step, is easy to operate, and does not require sintering synthesis at high temperature, and has the ability of large-scale production and the advantages of energy saving and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a charge and discharge curve diagram of a half-cell based on the lithium-rich manganese-based positive electrode material prepared in Example 1 and Example 2.

[0030] Figure 2 It is a half-cell charge and discharge cycle curve diagram of the lithium-rich manganese-based positive electrode material prepared based on Example 1 and Example 2.

[0031] Figure 3 This is a charge and discharge rate performance diagram of a half-cell based on the lithium-rich manganese-based positive electrode material prepared in Example 1 and Example 2.

[0032] Figure 4 Graph showing the high temperature cycle performance of a half-cell based on the lithium-rich manganese-based positive electrode material prepared in Example 1 and Example 2.

[0033] Figure 5 This is a charge and discharge cycle curve of a half-cell of a lithium-rich manganese-based positive electrode material prepared in Example 3 with a sulfur doping amount of 0.04 at%.

[0034] Figure 6 It is a comparison chart of half-cell charge and discharge cycle curves of the anionic sulfur-containing positive electrode material prepared in Example 2 and the polyanionic sulfate-doped lithium-rich manganese-based positive electrode material prepared in the comparative example. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings, but the protection scope and implementation of the present invention are not limited thereto. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Unless otherwise defined, all professional and scientific terms used have the same meanings as those familiar to those skilled in the art.

[0036] The performance of the positive electrode material prepared in the embodiment was measured by preparing a button battery;

[0037] The electrochemical performance of the positive electrode material is demonstrated by a button-type half-cell. The half-cell positive electrode is made of positive electrode material: conductive agent (Super P): binder (PVDF) in a mass ratio of 80:10:10.

[0038] The half-cell cathode preparation procedure is as follows: the cathode material is mixed with Super P, polyvinylidene fluoride PVDF to form a uniform powder mixture. The powder mixture is added to NMP and mixed to form a slurry. The slurry is applied to the aluminum foil current collector to form a thin film. The coated cathode electrode is dried at 90 ° C under vacuum for 6 hours to remove NMP. The dried aluminum foil coated with the cathode material is then cut into discs, weighed after rolling, dried at 110 ° C in a vacuum oven overnight, and finally transferred to an argon-filled glove box.

[0039] Preparation of button-type lithium battery: The prepared positive electrode is used as the positive electrode of the lithium battery, and the lithium sheet is used as the negative electrode. The electrolyte is the LB-372 high-voltage electrolyte of Duoduo Reagent Company. The diaphragm is the Whatman glass fiber diaphragm.

[0040] Example 1

[0041] Sulfur-free lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The specific steps for the preparation of O2 are as follows:

[0042] (1) According to the stoichiometric ratio of each element component in the chemical formula, 2.5709 g of lithium acetate monohydrate (5% excess), 0.6470 g of nickel acetate tetrahydrate, 0.6476 g of cobalt acetate tetrahydrate, and 2.6470 g of manganese acetate tetrahydrate were dissolved in 300 mL of deionized water, and 4.9656 g of ethylene glycol and 8.4056 g of citric acid monohydrate were added to obtain a mixed solution;

[0043] (2) evaporating the mixed solution on a rotary evaporator until it reaches a gel state;

[0044] (3) drying the obtained gel in a vacuum oven at 150° C. for 6 h to remove moisture;

[0045] (4) Grinding the obtained dried gel into powder, keeping the temperature at 450°C for 4 h in a tube furnace under air atmosphere, reacting at 900°C for 12 h, and cooling the furnace to obtain a lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.

[0046] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 was assembled into R2032 button half-cells and the charge and discharge tests were carried out at 30°C, 2.1-4.8V, and 0.1C. The charge and discharge curves are shown in Figure 1 The charge and discharge curve of sample S0 is given by Figure 1 It can be seen that the discharge capacity is 300 mAh / g.

[0047] Example 2

[0048] Liquid-phase doped anionic sulfur-rich lithium cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 The specific steps for preparation are as follows:

[0049] The lithium-rich manganese-based positive electrode material prepared in Example 1 was added to a 0.01 mol / L Na2S solution, with a ratio of the positive electrode material to the solution of 4 g / L. The mixture was stirred at 400 rpm for 30 minutes, filtered, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium-rich positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 .

[0050] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 Assemble into R2032 button half-cell, and perform charge and discharge test at 30℃, 2.1~4.8V, 0.1C. The charge and discharge curve is as follows Figure 1 The charge and discharge curve of sample S1 is given by Figure 1 It can be seen that the discharge capacity is 305 mAh / g, which is further improved compared with the undoped sulfur-rich lithium-rich positive electrode material sample S0 in Example 1.

[0051] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 Assembled into R2032 button half-cell, the charge and discharge test was carried out at 30℃, 2.1~4.8V, 1C. The cycle performance is as follows Figure 2 Medium sample S1. Figure 2 The cycle performance of sample S0 was tested under the same conditions using the undoped sulfur-rich lithium-rich cathode material in Example 1. Figure 2 Medium S0 samples, Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 The cycle life of lithium-rich manganese-based positive electrode materials has been significantly improved.

[0052] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 Assemble into R2032 button half-cell, and perform rate performance test at 30℃, 2.1~4.8V, such as Figure 3 Medium S1. Figure 3 The rate performance of sample S0 was tested under the same conditions using the undoped sulfur-rich lithium-rich cathode material in Example 1. Figure 3 Medium S0 samples, Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 The rate performance 1C exceeds 240mAh / g, which has been significantly improved.

[0053] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 Assemble into R2032 button half-cell, and perform cycle performance test at 55℃, 2.1~4.8V, 1C. Figure 4 As shown in S1. Figure 4 The high temperature performance of sample S0 was tested under the same conditions using the undoped sulfur-rich lithium-rich cathode material in Example 1. Figure 4 Medium S0 samples, Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 The high-temperature cycle performance is still over 250mAh / g after 50 cycles, and the stability has been significantly improved.

[0054] Example 3

[0055] Liquid-phase doped anionic sulfur-rich lithium cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.996 S 0.004 The specific steps for preparation are as follows:

[0056] The lithium-rich manganese-based positive electrode material prepared in Example 1 was added to a 0.02 mol / L Na2S solution, with a ratio of the positive electrode material to the solution of 4 g / L. The mixture was stirred at 400 rpm for 30 minutes, filtered, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium-rich positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.004 .

[0057] The obtained lithium-rich manganese-based cathode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.004 Assembled into R2032 button half-cell, the charge and discharge test was carried out at 30℃, 2.1~4.8V, 1C. The cycle performance is as follows Figure 5 As shown. Figure 5 It can be seen that after 200 cycles, the capacity is still 200 mAh / g, which has good cycle performance.

[0058] Comparative Example

[0059] Lithium-rich cathode materials doped with polyanion sulfate 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.992 (SO4) 0.002 The specific steps for preparation are as follows:

[0060] (1) The lithium-rich manganese-based positive electrode material prepared in Example 1 was added to a 0.01 mol / L Na2S solution, with the ratio of the positive electrode material to the solution being 4 g / L. The mixture was stirred at 400 rpm for 30 minutes, filtered, and dried in a vacuum oven at 120° C. for 12 hours to obtain a lithium-rich positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 .

[0061] (2) The obtained lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.998 S 0.002 The mixture was heated to 300°C in a muffle furnace for 5 h under oxygen flow to fully oxidize the sulfur element contained therein, thereby obtaining a lithium-rich positive electrode material Li doped with polyanion sulfate. 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 1.992 (SO4) 0.002 .

[0062] (3) The obtained lithium-rich positive electrode material doped with polyanion sulfate was assembled into a R2032 type button half-cell, and a charge and discharge test was performed at 30°C, 2.1-4.8V, and 1C, and the cycle performance was compared with that of Example 2. Figure 6 As shown. Figure 6 It can be seen that compared with the lithium-rich positive electrode materials doped with polyanion sulfate, the positive electrode materials doped with liquid phase anion sulfur are significantly more stable in cycling.

[0063] The above embodiments are only preferred embodiments of the present invention and are only intended to further describe the technical solutions of the present invention in detail. However, the protection scope and implementation methods of the present invention are not limited thereto. Any changes, combinations, deletions, replacements or modifications that do not deviate from the spirit of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sulfur-containing lithium battery positive electrode material, which is a lithium-rich manganese-based sulfur-doped positive electrode material with a chemical formula of Li 1+δ Mn a Ni b Co c S x O y ,in, δ=0~0.2,a=0.45~0.7,b=0.05~0.35,c=0.05~0.3,x=0.001~0.1,y=1.9~1.999,and x+y=2,δ+a+b+c=1;Sulfur is doped in the positive electrode material in the form of anions, and the positive electrode material Li that is not doped with sulfur is doped by a liquid phase method. 1+δ Mn a Ni b Co c O2 is fully reacted in a solution containing anionic sulfur, filtered, and dried to obtain a sulfur-containing lithium battery positive electrode material, wherein the anionic sulfur is S 2- .

2. The sulfur-containing lithium battery positive electrode material according to claim 1, characterized in that δ=0~0.2, a=0.45~0.7, b=0.05~0.35, c=0.05~0.3, x=0.001~0.05, y=1.95~1.

999.

3. The sulfur-containing lithium battery positive electrode material according to claim 1, characterized in that A solid solution or a nano-mixture of two phases is formed in the sulfur-containing lithium battery cathode material, namely zLiMO y S 2-y -(1-z)Li2MnO y S 2-y , where 0 < z < 1, M is a combination of metal elements with a valence higher than 2+ including Ni, Co, and Mn, and y = 1.9 to 1.

999.

4. The sulfur-containing lithium battery positive electrode material according to claim 1, characterized in that The sulfur-containing lithium battery positive electrode material is charged and discharged under the conditions of 30° C., 2.1-4.8V, and 0.1C, and the discharge capacity is greater than 300mAh / g; and is charged and discharged under the conditions of 30° C., 2.1-4.8V, and 1C, and the discharge capacity is more than 80% of the 0.1C discharge capacity.

5. The method for preparing the sulfur-containing lithium battery positive electrode material according to any one of claims 1 to 4, comprising adding a lithium-rich manganese-based lithium battery positive electrode material to a solution containing anionic sulfur for liquid phase reaction, stirring evenly, filtering to obtain the sulfur-containing lithium battery positive electrode material, and vacuum drying, wherein the general formula of the lithium-rich manganese-based lithium battery positive electrode material is Li 1+δ Mn a Ni b Co c O2, δ=0~0.2, a=0.45~0.7, b=0.05~0.35, c=0.05~0.3, δ+a+b+c=1.

6. The preparation method according to claim 5, characterized in that: The anionic sulfur-containing solution is a solution obtained by dissolving a soluble sulfur salt in a solvent.

7. The preparation method according to claim 6, characterized in that: The soluble salts of sulfur are sulfides.

8. The preparation method according to claim 5, characterized in that: The concentration of the solution containing anionic sulfur is 0.01 mol / L to 0.5 mol / L, and the anionic sulfur is S 2- .

9. The preparation method according to claim 5, characterized in that: The concentration range of the lithium-rich manganese-based lithium battery positive electrode material in the solution containing anionic sulfur is 0.002-0.01 g / mL; the stirring speed of the liquid phase reaction is 300-500 rpm, the reaction temperature is 30-40° C., and the time is 0.5-1 hour; the vacuum drying temperature is 100-150° C., and the drying time is 12-24 hours.

10. A lithium ion battery comprising a positive electrode material, a negative electrode material, a separator and an electrolyte, wherein the positive electrode material is the sulfur-containing lithium battery positive electrode material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Cation-anion codoped and modified layered lithium-rich anode material and preparation method thereof

    CN107579215A

  • Anion-cation co-doped modified lithium-rich manganese composite positive electrode material and preparation method thereof

    CN111370686A